Uncovering the Nexus between Language Culture and Identity Difference in the Context of Ethnic Self-Experience - Al Hakim, Muhammad Arif (Institut Agama Islam Negeri Kudus, 2021)
In this study of the language user, the connection between language culture and identity difference is examined from the ethnic context of language learning. This study aims to reveal the connection of those notions that is essential for language learners and will contribute to the development of language education. The research method of this study is autoethnography research. The author’s critical reflection as a reflective practitioner was used to elicit data by remembering and writing his personal experience. Then, the elicited data was analyzed using the theory of representation system, language culture, and identity difference. The findings of this study show that language, culture, identity, and difference have a robust linkage. The individual’s different culture and identity significantly affect the way he/she uses the language in certain contexts. Therefore, uncovering the interconnection of language culture and identity differences from critical self-reflection on ethnic-based experience may enrich a better understanding of the language learning process.